Sistem Pendukung Keputusan Pemilihan Televisi Menggunakan Metode Promethee - Limanto, Susana (Jurnal GEMATIKA, 2009)
Various facility, model, size and quality of television that are offered to the public can cause consumers to be confused to make decision about television that they want to buy. A web-based application program was developed to help consumers determine the best television based on their criteria. The application program is done by using Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). The application program will display at most, the most five eligible televisions. Evaluation result from 10 respondents who want to buy a television show that about 70% of respondents agreed that this application program can help them to determine the best television they want.